2010
DOI: 10.1111/j.1365-2478.2010.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Rock fracture compliance derived from time delays of elastic waves

Abstract: The purpose of this study is to compare the reliability of various methods of estimating normal rock fracture compliance from elastic wave measurements. We compare ultrasonic through‐transmission laboratory measurements for a smooth fracture in a Westerly granite specimen with numerical simulations and analytical solutions. The focus is on deriving compliance from time delays. The influence of specimen and source transducer width was constrained using numerical wave simulations. We find that measured ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Previous laboratory and numerical works have shown that the P wave transmission coefficient of a fracture can be linked to its mechanical compliance through the linear slip theory (Möllhoff et al, ; Pyrak‐Nolte & Nolte, ; Schoenberg, ). That is, fractures are modeled as nonwelded interfaces, across which traction is continuous but seismic displacement is not.…”
Section: Effect Of Individual Fractures On the Attenuation And Phase mentioning
confidence: 99%
“…Previous laboratory and numerical works have shown that the P wave transmission coefficient of a fracture can be linked to its mechanical compliance through the linear slip theory (Möllhoff et al, ; Pyrak‐Nolte & Nolte, ; Schoenberg, ). That is, fractures are modeled as nonwelded interfaces, across which traction is continuous but seismic displacement is not.…”
Section: Effect Of Individual Fractures On the Attenuation And Phase mentioning
confidence: 99%
“…Assume that hypotheses (6)(7)(8)(9) hold and ∈ [0, 1). Then, for initial data (u 0 , u 1 , g 0 ) ∈ , the Lamé system (5) possesses a unique weak solution (u, t u, z) ∈ C(R + ; ).…”
Section: Well-posednessmentioning
confidence: 99%
“…Assume that assumptions (6)(7)(8)(9)(10)(11) hold. Given a sequence { n } ⊂ (0, 1), let (u n , t u n , z n ) be the corresponding weak solution of (5) with n and initial data (u 0 , u 1 , g 0 ) ∈ .…”
Section: Theorem 32 (Limit Of Solutions)mentioning
confidence: 99%
“…The group arrival time was then used to calculate the group velocity. For a transmitted signal, the group time delay is always different from the first-break/onset delay (Möllhoff et al, 2010). First break indicates the first recorded transmitted signal attributed to the energy generated by the source, and group delay refers to the delay of the wave packet.…”
Section: Wavefront Imagingmentioning
confidence: 99%